AB0054 No evidence for premature immunosenescence in newly diagnosed, non treated, shared epitope-positive patients with rheumatoid arthritis. (23rd January 2014) - Chalan, P.; Kroesen, B.-J.; van der Geest, K.S.M.; Huitema, M.G.; Abdulahad, W.H.; Hepkema, B.; Brouwer, E.; Boots, A.
Abstract : Background: The peripheral T-cell pool in chronic autoimmune syndromes, such as Rheumatoid Arthritis (RA) displays features associated with senescence of the immune system. Immunosenescence is characterized by increased frequencies of terminally differentiated T lymphocytes defined as CD45RO-CCR7- (TEMRA ) or CD28null (and/or CD27null) cells. In addition, aged T cells produce pro-inflammatory cytokines (IFN-γ and TNF-α) (1, 2) and show an increased expression of NK receptors which is speculated to compensate for the loss of CD28 co-stimulatory signal (3). Previously, it has been suggested that carriers of the RA-associated HLA-DRB1 alleles containing the shared epitope (SE) sequence show signs of premature T-cell immunosenescence and that this is causally linked to the development of autoimmune pathology, as seen in RA (4). Objectives: 1) To elucidate if T-cell ageing is a feature of early RA; 2) to assess the relation between the presence of the RA-associated HLA-DRB1 shared epitope alleles and the number of TEMRA cells. Methods: PBMCs from recently diagnosed, non-treated RA patients (n=35) and age-/sex–/HLA-DRB1-matched healthy controls (HC, n=20) were stained with antibodies against CD4, CD8, CD45RO, CCR7. In addition, an extended phenotypic and functional analysis of T cells from 5 RA patients and 5 HC was performed by staining of senescence-associated surface markers (CD28, CD27, CD57, KLRG1, NKG2D, CD56, NKG2A and, CD94), intracellular cytokines (IFN-γ, TNF-α) and cytotoxic effector molecules (perforin, granzyme B). The presence of the SE+ HLA-DRB1 alleles was assessed by low-resolution PCR-SSOP typing for all the subjects included in the study. Results: The frequencies of CD4+ and CD8+ TEMRA lymphocytes (CD45RO-CCR7-) were not different between early-stage RA patients and HC. SE positivity was not associated with an increase of TEMRA in any of the studied groups. RA patients and HC showed similar frequencies of T cells with senescent phenotype defined based on CD28, CD27, CD57, KLRG1, CD56, CD94/NKG2A expression. Furthermore, T cells (both CD28+ and CD28-) from RA expressed IFN-γ, TNF-α, perforin and granzymeB at the same level as T cells from HC. Interestingly, CD8+CD28- T cells from RA patients showed increased expression of NK receptor NKG2D (median 96, 8% vs 74, 2% of NKG2D+ within CD8+CD28- in RA and HC, respectively). Conclusions: 1) The number of TEMRA lymphocytes is not altered in early-stage RA patients and is not dependent on the presence of the SE. Thus, the previously observed premature immune aging in RA is not causal to the disease but rather a consequence of the chronic inflammatory process. 2) The increased frequency of CD8+CD28-NKG2D+ T cells in early RA might be involved in the breakdown of immune tolerance. References: Thewissen M et al. Clin Immunol 2007, 123: 209-218. Fasth A.E.R. et al. Scand J Immunol 2004, 60: 199-208. Fasth A.E.R. et al. Eur J Immunol 2010. Schönland S.O. et al. PNAS 2003, 100: 13471-76. Disclosure of Interest: None Declared